From 20th century weddings to quarantine weddings: Old and new approaches to analyzing rituals - Balatonyi, Judit (UIN Sunan Gunung Djati Bandung, 2023)
Although ethnographic studies of marriage in 20th century Hungary have reckoned with the impact of socio-cultural transformations on getting married, nonetheless they primarily emphasized the normative aspects and permanence of the ritual; they stressed that marriage preserved “traditions”, or even that folk tradition acting as an ethno-folk-national “matrix” preserved and maintained the wedding rituals. Even if they touched upon the transformation of rituals, they primarily highlighted the modernization, simplification, fragmentation of the act of getting married and the marginalization of original meanings, traditional community norms, ideologies, and roles. Could this static and normative image depicting marriage not as a changing but rather as a decaying, diminished institution be in fact the result and consequence of an epistemological tradition, a methodological-theoretical focus that hides the process of the emergence of a new conception of marriage based on free choice, improvisation and on the idea of the individual breaking free of the yoke of normative traditions? The purpose of my paper is twofold. I will examine what the earlier Hungarian ethnographic studies understood by constancy, normativity, traditional or modern of wedding rituals. On the other hand, based on my current anthropological research (2019-2022, during the Covid–2019 pandemic) I will analyze the contemporary marriage rituals: and using the results of my research I also undertake a different kind of rereading of 20th century ethnographic descriptions. My paper based on the results of my digital anthropological research carried out between 2019 and 2022 (online questionnaires, digital ethnography, and in-depth interviews). I argue that the earlier Hungarian ethnographic approaches to weddings at the time may have been significantly influenced by prevailing Hungarian and international normative conceptualizations and theories of tradition and modernity.